PROMOTING SOCIAL MEDIA LITERACY AND STRENGTHENING SCHOOL RESOURCE CENTRES: A COMMUNITY-BASED SERVICE LEARNING STUDY IN MALAYSIA - Azmi, Nor Azlina; Selamat, Nordibradini; Said , Salasiah M; Shari, Sharunizam (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
The rapid growth of social media has reshaped how young learners in Malaysia access, share, and evaluate information, presenting both opportunities for collaboration and risks related to misinformation, online safety, and declining engagement with traditional literacy practices. School Resource Centres (SRCs) have been positioned as critical hubs for fostering information literacy, yet their effectiveness depends on student motivation and meaningful integration with digital platforms. This study evaluates the outcomes of a community-based Service Learning Malaysia-University for Society (SULAM) program aimed at strengthening social media literacy and enhancing SRC engagement among primary school students. Using a mixed-methods design, data were collected from 30 SRC prefects through pre–post surveys, structured observations, semi-structured interviews, and social media analytics. Quantitative findings indicate notable improvements in students’ confidence in sharing information online (+38.6%), use of social media for learning (+20%), and interest in literacy campaigns (+23.3%). Qualitative insights from the Guru Perpustakaan dan Media (GPM) revealed enduring recognition of NILAM and AINS programs, while highlighting persistent digital divides and uneven readiness for digital engagement. The integrative analysis suggests that structured service-learning interventions can reframe social media as a purposeful learning resource, build digital confidence, and reinforce SRCs as literacy ecosystems. However, the short duration, small sample, and absence of a control group limit generalizability. The study underscores the value of university–school partnerships in cultivating responsible digital citizenship, while calling for sustained, equitable investments in digital infrastructure and teacher capacity to maximize impact.